2021
DOI: 10.1007/s11356-021-15611-w
|View full text |Cite
|
Sign up to set email alerts
|

Separation of virgin plastic polymers and post-consumer mixed plastic waste by sinking-flotation technique

Abstract: The main objective of this research is to separate virgin polymers (PA, PC, PP, HDPE; PS, and ABS) and post-consumer plastic waste from municipal solid waste (MSW) using the sinking-flotation technique. Separation was carried out on a pilot scale in an 800-l useful volume container with 160 rpm agitation for one hour. Tap water, ethanol solutions, and sodium chloride at different concentrations were used as densification medium. Virgin polymers were separated into two groups: low-density (HDPE and PP) and high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…According to relevant research compiled in this systematic review, many gravity separation methods have been extensively investigated and employed for PVC recycling. These techniques include sink-float separation [27], hydrocyclone with suspension media [28,29], hydraulic separator [30], and jig separation [31,32], and they vary in terms of equipment requirements, operational parameters, and applications as summarized in Table 1.…”
Section: Gravity Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to relevant research compiled in this systematic review, many gravity separation methods have been extensively investigated and employed for PVC recycling. These techniques include sink-float separation [27], hydrocyclone with suspension media [28,29], hydraulic separator [30], and jig separation [31,32], and they vary in terms of equipment requirements, operational parameters, and applications as summarized in Table 1.…”
Section: Gravity Separationmentioning
confidence: 99%
“…The sink float separation technique was developed and has been employed as a method of separation based on varying the density of the aqueous media utilized during the density-based process. According to Quelal et al [27], multiple separation steps were needed with different media density (i.e., 1.000, 1.090, 1.100, and 1.175 g/cm 3 ) to separate post-consumer plastics including PVC, polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polystyrene (PS), and acrylonitrile butadiene styrene (ABS). These authors reported an approximately 84.6% recovery of each plastic using sodium hydroxide (NaOH) and tap water as an aqueous media for separation.…”
Section: Gravity Separationmentioning
confidence: 99%
“…Bill et al, 2022 [ 17 ] used solutions prepared with demineralised water and magnesium sulfate (MgSO 4 ) at different concentrations for sorting different plastic polymers. In the study by Meneses Quelal et al [ 18 ] the separation efficiency of plastics in aqueous solutions to which ethanol (C 2 H 6 O) and sodium chloride (NaCl) were added at different concentrations was evaluated, obtaining recovery rates ranging from 70% to 99.70% for virgin plastics.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Cleaner utilization of ASR is still of great challenges and significance. 11 Sorting and chemical recycling are generally considered the preferred methods, including foam flotation, 12 solvent separation, 13 gasification technology 14 and so forth. However, ASR is too complex to be sorted thoroughly, making it only possible for single or partial components such as metals, polyvinyl chloride.…”
Section: Introductionmentioning
confidence: 99%